Gcase and limp2 abnormalities in the liver of niemann pick type c mice - van der Lienden, Martijn J.C. (2021)
Funding Information: This work was supported by the NWO-Building Blocks of Life: GlcCer grant to J.M.F.G.A: BBOL-2007247202. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.